Long‐Term Glycemic Control in Adult Patients Undergoing Remote vs. Local Total Pancreatectomy With Islet Autotransplantation. (April 2017) - Kesseli, Samuel J; Wagar, Matthew; Jung, Min K; Smith, Kerrington D; Lin, Yu Kuei; Walsh, Matthew R; Hatipoglu, Betul; Freeman, Martin L; Pruett, Timothy L; Beilman, Gregory J; Sutherland, David E R; Dunn, Ty B; et al.
Abstract : OBJECTIVES: Total pancreatectomy with islet autotransplantation (TPIAT) is increasingly performed with remote islet cell processing and preparation, i.e., with islet cell isolation performed remotely from the primary surgical site at an appropriately equipped islet isolation facility. We aimed to determine whether TPIAT using remote islet isolation results in comparable long‐term glycemic outcomes compared with TPIAT performed with standard local isolation. METHODS: We performed a retrospective cohort study of adult patients who underwent TPIAT at three tertiary care centers from 2010 to 2013. Two centers performed remote isolation and one performed local isolation. Explanted pancreata in the remote cohort were transported ∼130 miles to and from islet isolation facilities. The primary outcome was insulin independence 1 year following transplant. RESULTS: Baseline characteristics were similar between groups except the remote cohort had higher preoperative hemoglobin A1c (HbA1c; 5.43 vs. 5.25, P =0.02) and there were more females in the local cohort (58% vs. 76%, P =0.049). At 1 year, 27% of remote and 32% of local patients were insulin independent ( P =0.48). Remote patients experienced a greater drop in fasting c‐peptide (−1.66 vs. −0.64, P =0.006) and a greater rise in HbA1c (1.65 vs. 0.99, P =0.014) at 1‐year follow‐up. A preoperative c‐peptide >2.7 (odds ratio (OR) 4.4, 95% confidence interval (CI) 1.6–14.3) and >3, 000 islet equivalents/kg (OR 11.0, 95% CI 3.2–37.3) were associated with one‐year insulin independence in the local group. CONCLUSIONS: At 1 year after TPIAT, patients undergoing remote surgery have equivalent rates of long‐term insulin independence compared with patients undergoing TPIAT locally, but metabolic control is superior with local isolation.